2007
DOI: 10.1002/jbm.a.31463
|View full text |Cite
|
Sign up to set email alerts
|

N‐halamine‐based chitosan: Preparation, characterization, and antimicrobial function

Abstract: Upon chlorine bleach treatment, amino groups in chitosan were transformed into N-halamine structures. The transformation was confirmed by UV/VIS, XPS, DSC, and TGA evaluation and iodimetric titration. The N-halalmine-based chitosan provided total kill of 10(8)-10(9) colony forming units (CFU/mL) of E. coli (gram-negative bacteria) and S. aureus (gram-positive bacteria) in 10 and 60 min, respectively. SEM observations demonstrated that the chlorinated chitosan effectively prevented the formation of bacterial bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
88
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(91 citation statements)
references
References 39 publications
2
88
0
1
Order By: Relevance
“…Antibacterial mechanism of N-halamines proposed till now can be classified mainly into two parts: (1) direct transfer of positive halogen from N Cl bond to the bacterial receptor [50][51][52] or (2) dissociation of positive halogen from N-halamine to solution with subsequent inactivation [53][54][55]. It is generally believed that N-halamines with stable N Cl bonds incline to the first mechanism, and N-halamines possessing less stable N Cl bonds easily dissociate halogen with "+1" oxidation state to water followed by attacking bacteria via the second mechanism [53].…”
Section: Resultsmentioning
confidence: 99%
“…Antibacterial mechanism of N-halamines proposed till now can be classified mainly into two parts: (1) direct transfer of positive halogen from N Cl bond to the bacterial receptor [50][51][52] or (2) dissociation of positive halogen from N-halamine to solution with subsequent inactivation [53][54][55]. It is generally believed that N-halamines with stable N Cl bonds incline to the first mechanism, and N-halamines possessing less stable N Cl bonds easily dissociate halogen with "+1" oxidation state to water followed by attacking bacteria via the second mechanism [53].…”
Section: Resultsmentioning
confidence: 99%
“…The chemical binding of chitosan to cellulose fibers can also be achieved by oxidation of cellulose fibers with potassium periodate under acidic conditions to form aldehyde groups, which are allowed to react with the amino groups of chitosan and form a Schiff base (C=N double bond) [37]. Following the model of N-halamine halogenation, some of the amino groups in chitosan have been transformed into an -NHCl structure in the presence of sodium hypochlorite [38]. It has been found that chlorination significantly improves the antimicrobial activity of chitosan.…”
Section: Fig 4 Chemical Structure Of Chitosanmentioning
confidence: 99%
“…Initiation and graft polymerization can occur during the drying step [30]. Chlorination treatment of chitosan has also been found to transform chitosan amino groups into N-halamines [29].…”
Section: N-halaminesmentioning
confidence: 99%
“…This mechanism consumes halogen atoms, but repeated halogenation treatments can refresh antibacterial function [29]. N-halamine precursors (radical initiators, such as hydantoin monomers) are often incorporated via textile finishing processes.…”
Section: N-halaminesmentioning
confidence: 99%